Remoção de sulfato de efluentes industriais integrando troca iônica e osmose inversa - Paulo Guilherme Freitas Melo (2024)
Sulfate (SO4 2- ) is a common ion present in natural water bodies in low concentrations. Increased sulfate load can cause direct and indirect damage to the environment in which it is found. In this context, the mining industry stands out as a source of increased concentration of this anion in bodies of water due to the existence of this substance in effluents from mineral processing routes. Currently, frequent chemistry, with the addition of calcium hydroxide (Ca(OH)2) to form calcium sulfate (CaSO4·2H2O), stands out as the most used process to treat this elimination. However, this method is still limited, as it does not allow concentrations below 1500 mg/l to be reached. The requirement under Brazilian legislation is the disposal of an effluent containing sulfate concentrations below 250 mg/l. Therefore, the present work aimed to investigate alternative routes for removing sulfate from an effluent mining model, using instructions, membrane separation processes and ion exchange. The reverse osmosis tests were extended using the commercial BW30 Filmtec membrane and the ion exchange tests using commercial anionic (Purolite A400) and cationic (Purolite C100) resins in an experimental laboratory setup. The section of a sodium sulfate solution using CaCl2 and Al(OH)3 was reflected in a mixture of calcium carbonate and aluminum hydroxide, with the sulfate content reduced by the dilution effect. Ion exchange proved promising, achieving 46.6% sulfate removal from the wet sodium sulfate solution. Experiments with reverse osmosis demonstrated permeate results below 250 mg/l, with the exclusion of 94% of sulfate from the feed. However, problems of permeate flux reduction by 52.4% were observed when tests were carried out on the mining solution, containing metal ions. The combination of ion exchange and reverse osmosis revealed that the presence of other ions considerably impairs sulfate removal, probably due to an increase in the total ionic concentration, and, consequently, in the osmotic pressure of the solution, so that the sulfate content was reduced. from 1500 mg/l to 1053 mg/l, i.e. 30%. These results highlight the importance of careful method selection and attention to operational challenges when treating sulfate-containing wastewater.